On Fučik spectra for third order equations - Sergejeva, Natalija (Mathematical Modelling and Analysis, 2007)
We construct the Fučik spectrum for some third order nonlinear boundary value problems. This spectrum differs essentially from the known Fučik spectra.First Published Online: 14 Oct 2010